Glypican-3 and Hep Par-1 are Useful Biomarkers in the Cytologic Assessment of Ascites. Issue 1 (January 2019) - Cabibi, Daniela; Bisanti, Andrea; Lanza, Dorotea; Brucculeri, Vanessa; Porcasi, Rossana; Ingrao, Sabrina; Midiri, Federico; Picone, Dario; Giannone, Antonino Giulio
Abstract : Till date, the utility of cytologic assessment of ascites for the identification of hepatocellular carcinoma (HCC) cells is still debated and the usefulness of immunocytochemistry for glypican-3 (GPC3) and Hep Par-1 in this setting has not been reported. Liquid-based cytology of ascitic fluid of 28 cirrhotic patients was performed and the spots obtained were stained with hematoxylin and eosin, papanicolau, and with GPC3 and Hep Par-1 antibodies. GPC3 and Hep Par-1 antibodies stained positively the atypical cells in the ascites of 2 patients with HCC showing an exophytic growth pattern. The specimens of the patients with nonexophytic HCC, other non-HCC cancers, or cirrhosis stained negatively. We hypothesize a relationship with the exophytic growth of the tumor. Thus, GPC3 and Hep Par-1 are useful in the cytologic assessment of peritoneal effusions to distinguish mesothelial cells and neoplastic non-HCC cells from HCC cells, presence of which, however, represent a very rare event. This is the first study in which GPC3 and Hep Par-1 immunostaining has been used in the cytologic assessment of HCC ascites.